Trigonometric Approximation of Functions in Weighted L^p Spaces - Guven, Ali (Sarajevo Journal of Mathematics, 2024)
The approximation properties of means of trigonometric Fourier series in weighted L^p spaces ( 1<p<∞ ) with Muckenhoupt weights are investigated. 2000 Mathematics Subject Classification. 41A25, 42A10